Amyloid‐β Oligomer‐Targeted Gadolinium‐Based NIR/MR Dual‐Modal Theranostic Nanoprobe for Alzheimer's Disease. (24th February 2020) - Wang, Chengke; Wang, Xueli; Chan, Hei‐Nga; Liu, Guifeng; Wang, Zhenxin; Li, Hung‐Wing; Wong, Man Shing
Abstract: While the deposition of amyloid‐β (Aβ) plaques is one of the main pathological hallmarks of incurable Alzheimer's disease (AD), Aβ oligomers have been identified as a more appealing AD biomarker due to their being more pathogenic and neurotoxic. Therefore, the development of a sensitive and effective technique for oligomeric Aβ detection and imaging is beneficial for the early detection of AD, monitoring disease progression, and assessing the efficacy of potential AD drugs. Herein, the development and investigation of the first Aβ oligomer‐specific Gd 3+ ‐based nanoparticles (NPs), NP@SiO2 @F‐SLOH as a multimodal near‐infrared imaging (NIRI)/T1 ‐weighted magnetic resonance imaging (MRI) contrast agent for real‐time visualization of Aβ contents in an AD mouse model is reported. Remarkably, the NP@SiO2 @F‐SLOH is successfully applied for in vivo and ex vivo NIRI with high sensitivity and selectivity for Aβ oligomers and for MRI with good spatial resolution in different age groups in an AD mouse model. Furthermore, the NP probe exhibits a noticeable inhibitory effect on Aβ fibrillation and neuroprotection against Aβ‐induced toxicity indicating its desirable therapeutic potential for AD. All these results illustrate the tremendous potential of this versatile and sensitive nanomaterial as an effective theranostic MRI nanoprobe for practical use. Abstract : Amyloid‐β (Aβ) oligomer‐targeted F‐SLOH surface functionalized gadolinium‐based nanoparticles have been successfully synthesized and applied for the detection and visualization of Aβ content in an Alzheimer's disease (AD) mouse model at different age groups using in vivo near‐infrared and magnetic resonance dual‐modal imaging and inhibiting the Aβ aggregation and reactive oxygen species generation, resulting in versatile theranostic nanoprobe for AD.